Evaluation of serum Cystatin C as a predictor of eGFR in type 2 diabetic patients with nephropathy - Aqsa Fatima; Pooran Mal; Zoheb Rafique Memon; Mukesh Kumar; Haseeb Jameel Memon,; Misbah Fatima (Journal of Shalamar Medical & Dental College)
Background: Diabetic nephropathy (DN) is the leading cause of chronic kidney disease (CKD) worldwide.